دور التخطيط الاستراتيجي في خلق الميزة التنافسية في المؤسسة الاقتصادية - وئام, باباي; رانية, العايز (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة التي قمنا بها إلى معرفة دور التخطيط الاستراتيجي في خلق الميزة التنافسية للمؤسسة، حيث تكون مجتمع الدراسة من موظفي مؤسسة )رغوة الجنوب –تقرت(-ولغرض تحقيق أهداف الدراسة تم تصميم استبانة واستخدام الأساليب الإحصائية الملائمة )الاعتماد على برنامج إحصائي، (spss)، وتمت معالجة إشكالية الدراسة بتناول فصل أول يتضمن الإطار النظري للتخطيط الاستراتيجي والميزة التنافسية، وفي الفصل الثاني تطرقنا إلى دراسة حالة مؤسسة )رغوة الجنوب- تقرت-(.من خلال الدراسة النظرية والتطبيقية تم التوصل إلى جملة من النتائج أهمها سعي المؤسسة محل الدراسة إلى تحقيق الميزة التنافسية ، بالإضافة إلى أنه اتضح أن ممارسة التخطيط الاستراتيجي الكلي والتخطيط الاستراتيجي لوحدات الأعمال وكذلك التخطيط الاستراتيجي الوظيفي والتشغيلي دور في خلق الميزة التنافسية محل الدراسة. This study, which we conducted, aims to know the role of strategic planning in creating the competitive advantage of the institution, where the study population consisted ofthe employees of the (South foam -Touggourt) In order to achieve the objectives of the study, a questionnaire was designed and the appropriate statistical methods were used (relying on a statistical program ,(spss) ,The problem of the study was addressed by addressing the first chapter that includes the theoretical framework for strategic planning and competitive advantage. In the second chapter, we dealt with a case study of the institution (South foam - Touggourt -).through theoretical and applied studies, a number of results were reached ,the most important of which is the pursuit of the institution under study to achieve a competitive advantage, well it turns out that the practice of overall strategic planning ,strategic planning for business unites ,as well as functional and operational strategic planning have a role in creating the competitive advantage under study.
Keywords: تخطيط، تخطيط استراتيجي، تنافسية، ميزة تنافسية، مؤسسة رغوة الجنوب.; "Planning, strategic planning, competitive, competitive advantage, south foam ،mattresses corporation"